Investigating the Antecedents of Green Society Satisfaction (GSS): Collaborative Good Government Practices (CGGP) as Mediating Variable An Empirical Study in Pontianak City - Kardison Lumban Batu; Ade M. Yuardani (TRANSFORMASI: Jurnal Manajemen Pemerintahan, 2020)
In streamlining and making services efficiently to the community the local government is demanded to be able to make service innovations that support the improvement of the quality of services to the community. Service quality relates to products, services, people, processes and the environment that can meet the needs of those who receive these services. The aim of current research is investigating the antecedents of Green Society Satisfaction (GSS) mediated by Collaborative Good Government Practices. Structural Equation Modeling with AMOS is deployed to analyze the data. Data collecting method is survey with distributing questionnaires. A large number of sample is required, where the society in pontianak as the population. Some criterions are designed in order to obtain wanted samples. Purposed sampling is used with non-purposive sampling technique. Cronbach’s Alpha values, Regression Weights, Absolute, Incremental, Parsimony Fit Measurements, and Variables, Standardized Loading, α, Error, CR and EVA are within rule of thumbs. The research findings demonstrated that all proposed hypotheses are accepted. Reliability Advantages, Responsiveness Advantages, Assurance Capability, Empathy and Tangibles respectively show the positive significant as the antecedent of Green Society Satisfaction mediated by Collaborative Good Government Practices. This is to claim that government offices have deeply taken into consideration that good government practices is a must in delivering and offering services. Keywords: Reliability Advantages, Responsiveness Advantages, Assurance Capability, Empathy, Tangibles, Collaborative Good Government Practices, Green Society Satisfaction